2017
DOI: 10.1038/srep40220
|View full text |Cite
|
Sign up to set email alerts
|

High fat diet-induced changes of mouse hepatic transcription and enhancer activity can be reversed by subsequent weight loss

Abstract: Epigenetic factors have been suggested to play an important role in metabolic memory by trapping and maintaining initial metabolic changes within the transcriptional regulatory machinery. In this study we fed mice a high fat diet (HFD) for seven weeks followed by additional five weeks of chow, to identify HFD-mediated changes to the hepatic transcriptional program that may persist after weight loss. Mice fed a HFD displayed increased fasting insulin levels, hepatosteatosis and major changes in hepatic gene tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 59 publications
(85 reference statements)
4
74
0
1
Order By: Relevance
“…Gene ontology analysis of HFD-upregulated and -downregulated (LFD-upregulated) genes showed that, consistent with previous bulk gene expression studies (28)(29)(30), genes controlling lipid and fatty acid metabolism are upregulated in HFD, while genes controlling amino acid and drug catabolism are downregulated (…”
Section: Hfd Alters Expression Of Genes Controlling Lipid Metabolismsupporting
confidence: 86%
See 1 more Smart Citation
“…Gene ontology analysis of HFD-upregulated and -downregulated (LFD-upregulated) genes showed that, consistent with previous bulk gene expression studies (28)(29)(30), genes controlling lipid and fatty acid metabolism are upregulated in HFD, while genes controlling amino acid and drug catabolism are downregulated (…”
Section: Hfd Alters Expression Of Genes Controlling Lipid Metabolismsupporting
confidence: 86%
“…Importantly, PPAR is known to be activated upon stimulation with fatty acids, as they are direct ligands for transcriptional activation of PPAR (42,43). Former bulk analysis of fatty liver transcriptome also revealed that various targets of PPAR, as represented in our dataset, are strongly upregulated upon HFD challenges (28)(29)(30)45). Notably, many of these genes did not show such diet-dependent modulations in Ppara-deleted knockout mutant strains (44,45).…”
Section: Discussionmentioning
confidence: 75%
“…Treatment with the histone deacetylase inhibitor trichostatine A increased KLK7 expression in pancreatic (Panc-1) and cervical (HeLa) cancer cell lines [61]. Importantly, HFD-induced changes seem to be readily reversible after weight-loss, as reported for hepatic epigenetic changes induced after 7 weeks of HFD in mice [62], and HFD-induced DNA-hypermethylation could also be suppressed via exercise in mice [57]. DNA methylation in the promoter regions of the vaspin gene in WAT and BAT has not been investigated previously.…”
Section: Discussionmentioning
confidence: 73%
“…Changes in epigenetic modifications and transcriptional regulation are essential for phenotypic adaptation of cell types to environments, including high-fat diet (HFD) [15][16][17]. Since some DNA-binding proteins play a role in triggering epigenetic reprogramming in specific genomic regions [18], we hypothesised that the corresponding sequence motifs could be enriched in cis-regulatory regions with local epigenetic alterations in response to environmental stimuli.…”
Section: Introductionmentioning
confidence: 99%